Information focus, syntactic weight and postverbal constituent order in Spanish - Heidinger, Steffen (Borealis – An International Journal of Hispanic Linguistics, 2013)
In Spanish, postverbal constituents – such as direct object, locative adjunct or depicitive – can be ordered in different ways (e.g. Juan bailó desnudo en su casa vs. Juan bailó en su casa desnudo). The present paper examines two possible factors for postverbal constituent order: information focus and syntactic weight. Based on data from a perception experiment it will be shown that information focus and syntactic weight indeed influence in postverbal constituent order in Spanish: both the focalization of a constituent and the increase of the weight of a constituent increase the frequency with which the respective constituent takes up the sentence final position. As concerns the strength of the two factors, our results suggest that information focus and syntactic weight influence in postverbal constituent order to a similar extent. As concerns the syntatic position of narrow information focus in Spanish, our results show that the sentence final position is the preferred position for narrowly focused constituents, but such constituents are not limited to the sentence final position. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE <![endif]--><!--[endif] --><!--[if gte mso 9]> <![endif]--><!--[endif] -->